MOBILE-BASED VACCINATION DATA COLLECTION APPLICATION IN SUKADADI VILLAGE - Rika Irma Yanti; Sri Ipnuwati (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2021)
Vaccination data collection in Sukadadi village is a very important thing to record every resident who has and will carry out vaccinations to overcome and prevent the spread of the COVID-19 virus. Previous research has produced an application that can help the process of collecting vakksination data and contact tracing more accurately and on time and flexibly can be updated in real time so that the process of collecting vakksination data and contact tracing can be accessed by residents and local village officials This research aims to help residents of Sukadadi village in collecting vaccination data that will and has been carried out by local residents using the system Recently, village officials and medical officers in Sukadadi village will find it easier to collect data quickly and computed so that the data produced is more accurate, precise and can be accessed by the community